«Моя робота — допомагати мамі»: Діти ультраортодоксальних єврейських общин в Ізраїлі - Блюмен, О. (Народна творчість та етнографія, 2008)
Children's housework is rarely recognized as work and seldom studied, and children's understanding of their involvement in unpaid work in the family is typically overlooked. Children's housework in the ultraorthodox Jewish community in Israel was explored in regard to where specific chores were performed, and how they were viewed and interpreted by children. Findings show that children define their housework as work, and that they and their housework are supervised by unfamiliar adults. The analysis reveals adults' dependence on children's housework.